Assessment of Water Quality and Its Effects on Human Health in Ruiri/Rwarera Ward, Meru County, Kenya - Muite, Joseph Kathurima (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Water quality includes Physical, chemical and biological characteristics based on the standards of its usage. It is one of the main indicators of the quality of life provided to consumers. Water quality impacts both the public health and aesthetic value of a consumable product. Inadequate management of industrial and agricultural wastewater means the drinking water of hundreds of millions of people is dangerously contaminated or chemically polluted. The natural presence of chemicals, particularly in groundwater, can also be of health significance, including arsenic and fluoride. In contrast, other chemicals, such as lead, may be elevated in drinking water as a result of leaching from water supply components in contact with drinking water. The main objective of study is to access the water quality and its effects on health in Ruiri/Rwarera ward in Buuri - sub county Meru County in Kenya. The study will involve onsite and laboratory tests which will all be aimed to get the water content from different water sources. The study area is the Ruiri/Rwarera ward, which is situated in the Buuri sub-county in Meru County, Kenya. It has an area of approximately 131.50 square kilometers and a population of 18,754 people. The main source of drinking water from the study area includes; the boreholes, springs, aquifers, rain water among other sources. Many of these sources get polluted so fast.. Research on the assessment of water quality and its effects on health in the Ruiri/Rwarera ward has not been done before. Hence, the study will be useful for policy-making by the county government of Meru in Kenya. The objectives of this research is to establish biological pollutants, chemical pollutants and methods of water treatment used by the residents in domestic water sources and to access the water treatment methods used by the ward authorities and residents to treat domestic water in the area of study. This research study will address these gaps by discovering the extent of water pollution for domestic water in the Ruiri/Rwarera ward. Water samples collected from the field of study will be analyzed in Laboratory by use of equipment’s like spectrophotometers, chromatographs and mass spectrometers in order to identify and quantify different pollutants. Quantitative data will be collected using a structured research questionnaire. The collected data from the laboratory will be entered into the computer and analyzed by Statistical Package for Social Sciences (SPSS) and Microsoft excel. The results will be presented in percentages, tables and chats. The expected results will be a detailed analytical analysis of water content and retrospective data on water related diseases from the area of study. The study will help the county government and other stakeholders to intervene on matters of water hygiene.